ST36 POINT ACUPRESSURE METHOD AS AN EFFORT TO MANAGE THE EVENTS OF EMESIS GRAVIDARUM IN THE 1st TRIMESTER PREGNANT WOMEN: Happy Firliya, Widia Shofa Ilmiah, Maria Veronika Widiatrilupi - Happy Firliya Awal; Widia Shofa Ilmiah; Raden Maria Veronika Widiatrilupi (Jurnal Kesehatan Hesti Wira Sakti, 2023)
The most typical main complaint experienced by pregnant women practically everywhere in the globe is emesis gravidarum. Variations in high hCG levels are a factor in emesis gravidarum. In Indonesia, 50–85% of pregnant women experience this condition. According to other research, 60–80% of primigravida and 40–60% of multigravida develop emesis gravidarum. The study was conducted at PMB Wartini Rejoyoso to examine the effects of acupressure point ST36 treatments on emesis gravidarum in first-trimester pregnant women. Pra experimental design. The population of all first-trimester pregnant women at Independent Practice Midwife (PMB) Wartini Rejoyoso who experienced emesis gravidarum was 26 people, and the samples were 16 each of acupressure SOP and PUQE-24. instrumentation, a 7-minute intervention every morning for 7 days, and Wilcoxon Match Pairs Test data analysis. According to the data, there was significant emesis in 62.5 percent of people prior to the intervention and mild emesis in 93.8 percent of people after it, with a p value of 0.03 to α 0.05. Conclusion: ST36 acupressure may have an impact on the frequency of emesis gravidarum in the first trimester. When feeling queasy or sick, pregnant women are expected to apply acupressure to ST36. Keywords: Acupressure Point ST 36, Emesis Gravidarum, First Trimester